Metastatic Thyroid Cancer Presenting as Renal Cortical Mass - Osamah Hasan; Matthew Houlihan; Tobias S. Kohler; Courtney M. P. Hollowell (Case Reports in Urology)
The authors present a rare case of primary diagnosis of metastatic, differentiated thyroid cancer presenting as a solitary, large renal mass. Renal cortical masses which represent metastatic primary malignancies are often small, multifocal, and in the setting of active malignancy. Surgical excision of this patient’s renal mass demonstrated the unexpected diagnosis and subsequent endocrine surgical intervention.